Proper fund size: a perspective from both investors and fund managers. Issue 5 (4th May 2022) - Zhang, Linlin; Jiang, Jiajun; An, Yunbi
Abstract : This paper proposes the notion of the proper size interval for funds and the market redemption return in fund markets. We establish a model to determine the proper size interval that accounts for the interests of both investors and fund managers as well as market constraints. We then propose a method to analyze fund managers' abilities and fund sizes compared to the market averages. Using data on Chinese equity and hybrid funds for the sample period from 2009 to 2019, we find that there is a negative log-linear relationship between fund net excess return and fund size. Our model shows that both equity and hybrid funds experience the transition from being over-sized to properly- and under-sized. Under-sized and over-sized funds account for about 60% and 30% of the total sample, respectively, while less than 10% of funds have a proper size. Compared with over- or under-sized funds, funds with a proper size can generate higher returns and higher capital inflow. Our empirical results confirm that funds with higher managerial ability indeed outperform those funds with lower managerial ability, regardless of the category of fund size. Overall, our model provides a new method for fund investors, managers, and regulators to classify and evaluate funds.